The Study of the Performance of the Diamond Wheel’s Steel and CFRP Hubs in Tungsten Carbide (WC) Grinding - Yao-Tsung Lin; Kai-Jung Chen; Chun-Yen Chen; You-Xhiang Lin; Ming-Yi Tsai (Applied Sciences, 2023)
Tungsten carbide (WC) has been widely utilized in recent years in the hardware, mechanical, and chemical industries and in national defense because of its high hardness, anti-wear, low temperature, and anti-corrosion properties. However, using it for grinding is also challenging because the WC material has high hardness and brittle characteristics. The typical hub of a diamond wheel is made of steel. In high-speed grinding, the steel hub of the diamond wheel is subjected to gravity and centrifugal forces, which cause grinding wheel vibration, poor workpiece processing quality, and a short machine life. Therefore, this study used a carbon-fiber-reinforced thermoplastic (CFRP) hub to replace the steel hub when grinding the WC workpiece. It aimed to investigate methods to reduce oscillation, improve chip efficiency, and increase accuracy in the WC workpiece. The research results demonstrated that using a CFRP hub in the grinding wheel can reduce the oscillation when the peripheral speed of the grinding wheel is at 20–100 m/s. Additionally, the surface roughness average (Ra) of the workpiece can be reduced to 3.2–25.4% and the ten-point height of irregularities (Rz) can be reduced to 18.9–44% compared to using a steel hub in the grinding wheel.